WYKŁADNIA TESTAMENTÓW NOTARIALNYCH - Pałdyna, Tomasz (Zeszyty Prawnicze, 2017)
INTERPRETATION OF TESTAMENTS MADE BEFORE A NOTARY Summary The article deals with problems connected with interpretation of testaments made before a notary. Following a brief introduction describing the notion of a testament as well as characteristics of this legal transaction and general remarks on a testament form, including a notary act form, the article focuses on interpretation of a testators declaration pointing at basic rules which should govern interpretation of a last will included in a notary act. Testament’s interpretation aim is to establish testator’s actual will recorded in the testament. Real life experience shows that many a time testamentary dispositions are very imprecise not to say unclear. Interpretation problems occur more often with personally written testaments than with testaments made before a notary thanks to professional knowledge of a person participating in preparation of a „last will” statement. A notary who takes down in writing bequeather’s will is working with him / her on the wording of the declaration of will. However, it happens that formulation of notarial will also raises doubts about bequeather’s actual will. For notarial wills, the rules stated in Article 948 of the Civil Code are binding, with the assumption of the testament „co-author’s” professionalism. Participation of a notary in drawing up a testament implies that law or legal terms included in the document carry the meaning used by legislators (Acc. to: E. Skowrońska, comments on SN law of 16 September 1993, III CZP 122/93, published in OSP in 1994 year, no. 10, item 177) and lawyers in their register. In case of contradictory content of a notarial will, by using the above mentioned interpretation principle, the interpretation results established for such a declaration of will could be very different from those established, if testator’s last will was expressed in a personally written testament. Thus, apparently, not only the testament’s content but also its form may influence interpretation result. Sometimes, a testament made before a notary uses plain language inappropriately. Testament’s content may include records understandable only to the testator and people from his/her surroundings. A testator may, even unintentionally, mislead a notary about his/her actual will. For notarial wills, the problem of ignorance of law is ruled out. This applies particularly to a rule of law concerning succession, but also to different ones (for example, to a rule concerning property regulations). It is assumed that a bequeather realizes consequences of his/her dispositions. He should be instructed about the consequences by a notary (Art. 80 § 3 of the Law on Notary Public). Therefore, in case of ambiguity (art. 948, paragraph 2 of the Civil Code) the interpretation which is rational not only from life but also from legal perspective, should be given precedence. For testaments prepared by a testator personally, presumption of knowledge of law is not valid. Beginning interpretation of declaration of will included in a notary act we assume that bequeather’s disposition is lawful and consistent with the rules of social intercourse, and that it does not aim to evade the law (article 58 of the Civil Code). A notary is obliged to refuse performance of transaction which is against the law (Art. 81 of the Law on Notary Public). As for testaments made before a notary, it may well be assumed that a document tendered in court is the testament of the person concerned (actually, it is an extract from the document) (Contradictory thesis requires refutation of presumption according to art. 247 of the Civil Proceeding’s Code), and also, that at the moment of drawing up the testament the testator had ability to bequeath and that his/her declaration of will is not defective. It should also be assumed that for testaments made before a notary a plea of lack of will to testate may be raised in very exceptional situations.